Theoretical investigation of intrinsic point defects and the oxygen migration behavior in rare earth hafnates. Issue 11 (1st June 2021) - Wang, Peiying; Zhao, Juanli; Fan, Yun; Zhang, Wei; Cui, Yuanyuan; Zhang, Liangmiao; Liu, Bin; Nian, Hongqiang; Li, Yiran
Abstract: In this work, the composition-dependent point defect types and formation energies of RE 2 Hf2 O7 ( RE = La, Ce, Pr, Nd, Pm, Sm, Eu and Gd) as well as the oxygen diffusion behavior are systematically investigated by first-principles calculations. The possible defect reactions and dominant defect complexes under stoichiometric and non-stoichiometric conditions are revealed. It is found that O Frenkel pairs are the predominant defect in stoichiometric pyrochlore hafnates. Hf- RE cation anti-site defects, accompanied by RE vacancies and/or oxygen interstitials, are stable in the non-stoichiometric case of HfO2 excess. On the other hand, RE -Hf anti-site defects together with oxygen vacancies and/or RE interstitials are preferable in the case of RE 2 O3 excess. The energy barriers for the migration along the VO4 8 f - VO48 f pathway of pyrochlore hafnates were calculated to be between 0.81 eV and 0.89 eV. Based on these results, a defect engineering strategy is proposed and the pyrochlore hafnates investigated here are predicted to exhibit potential oxygen ionic conductivity. Graphical abstract: Image 1 Highlights: O Frenkel pairs and cation antisite defects are the predominant defect types in stoichiometric rare earth hafnates. Hf R E . together with V R E ‴ and/or O i ″ is energetically favorable in HfO2 rich condition, while R E Hf ′ together with V O .. and R E i … is preferred in RE 2 O3 rich case. The migration barriers of V O .. of rare earth hafnates are predicted to be 0.81 eV ∼ 0.89 eV.